THE FINANCING POTENTIAL OF ENTERPRISE’S AUTOSANATION AS THE MAIN STRUCTURAL ELEMENT OF ITS AUTOSANATION CAPACITY - Яцюк, Олег (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article examines the economic essence of the financing potential of autosanation as the main structural element of the enterpise's autosanation capacity. It has been established that in Ukrainian and foreign scientific literature, there is no proper coverage of the issues of formation and realization of the financing potential of enterprise’s autosanation. The author considered the system of financial support of the enterpise's autosanation, revealed the relationship between the forms and sources of its internal and external financing. On the basis of the conducted research, a decomposition of enterprise’s autosanation capacity is proposed and its components are analyzed. The author defines the financing potential of autosanation as the presence of internal and external sources of financing sanation measures and opportunities for their mobilization and use in the process of financial recovery. This potential can be found both in the field of financing (in the form of unused financing opportunities) and in the production field (in the form of cost reduction or investment payments, etc.). The financing potential of autosanation is the most important structural element of autosanation capacity, which the author defines as the presence of an enterprise that is in a financial crisis or threatened by a crisis, with financial, organizational, legal, and production- technical capabilities to implement a system of measures that must be implemented by the management, owners and employees of the enterprise using internal and external sources of financing and which ensure the ability to successfully carry out its financial recovery or eliminate the threat of a crisis. In the author's opinion, the definitions of the financing potential of autosanation and the company's autosanation capacity formulated in the work adequately and fully reflect the economic essence of these concepts.